2019
DOI: 10.1002/iju5.12078
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous metastasis of prostate carcinoma treated with electron radiotherapy

Abstract: Introduction: Prostate carcinoma is typically diagnosed and treated, and it rarely manifests as cutaneous metastases. We herein report electron radiotherapy for the treatment of cutaneous metastases causing cellulitis, with a durable clinical response achieved. Case presentation: A 70-year-old male patient with scrotal cutaneous metastasis of prostate carcinoma was undergoing treatment with docetaxel chemotherapy due to recurring cellulitis originating from the scrotum, and his treatment was interrupted. We ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
(5 reference statements)
0
5
0
Order By: Relevance
“…Arase et al reported a case of cutaneous metastasis to the chest wall from prostate adenocarcinoma. In the case, durable tumor shrinkage and symptom relief were achieved after radiation therapy using 18 Gy in 3 fractions using electron 9 . Oike et al reported a case of cutaneous metastasis of non‐small cell lung cancer to the arm.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Arase et al reported a case of cutaneous metastasis to the chest wall from prostate adenocarcinoma. In the case, durable tumor shrinkage and symptom relief were achieved after radiation therapy using 18 Gy in 3 fractions using electron 9 . Oike et al reported a case of cutaneous metastasis of non‐small cell lung cancer to the arm.…”
Section: Discussionmentioning
confidence: 97%
“…In the case, durable tumor shrinkage and symptom relief were achieved after radiation therapy using 18 Gy in 3 fractions using electron. 9 Oike et al reported a case of cutaneous metastasis of non‐small cell lung cancer to the arm. In that case, photon radiation therapy at 45 Gy in 15 fractions led to complete tumor remission and improved the patient's quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…In the case, durable tumor shrinkage and symptom relief was achieved after radiation therapy using 18 Gy in 3 fractions using electron. 9 Oike et al . reported a case of cutaneous metastasis of non-small cell lung cancer to the arm.…”
Section: Discussionmentioning
confidence: 99%
“…Electron radiation therapy has been employed as an effective palliative treatment for painful skin metastases. 21 , 22 Surgical excision and intralesional chemotherapy are also viable options for small and limited metastases. 9 , 10 Systemic chemotherapy has the advantage of potentially reducing the primary malignancy as well as visceral and osseous metastases.…”
Section: Discussionmentioning
confidence: 99%